When Does Brace Noncompliance Occur in Patients with Clubfoot Deformity? - Doski, Jagar (Clinics in orthopedic surgery, 2025)
Background: Noncompliance with bracing and its protocol is the most common cause of clubfoot deformity relapse after correction. The literature does not clarify when patient noncompliance with the brace occurs—during which period of the bracing phase, or in which age group. This study aimed to determine when noncompliance is most likely to occur. Methods: This descriptive observational study included children with idiopathic talipes equinovarus deformity for whom the foot abduction brace was applied to their feet after complete correction via the Ponseti method. Each patient was observed until the end of the brace-wearing program (at the end of the fourth year) and had 18 follow-up appointments. The patient’s age and compliance (yes or no) were recorded at each appointment. Results: Thirty-four cases (21 males and 13 females) with 58 feet were included in the current study. The mean age at the time of deformity correction and commencement of the brace was 2.3 months (standard deviation [SD], 0.6 months), and that at the final follow-up appointment was 50.6 months (SD, 0.9 months). Noncompliance occurred in 11 of 34 cases (32.4%). It started after the end of the first year of life, when the mean age of the patients was 14.6 months (SD, 0.8 months). A prominent rise in noncompliance was observed after the end of the second year of life, when the mean age was 26.6 months (SD, 0.9; 95% CI, 26.3–26.9). There was a significant positive correlation between instances of noncompliance and both the number of brace phase appointments and the age of the patient (p < 0.001). Conclusions: Noncompliance with foot abduction brace started at the end of the first year and peaked after the end of the second year. KCI Citation Count: 0